2023
DOI: 10.1111/os.13624
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Nottingham Hip Fracture Score in Predicting Postoperative Outcomes Following Hip Fracture Surgery

Abstract: Objective: Although several prognostic models have been developed for patients who underwent hip fracture surgery, their preoperative performance was insufficiently validated. We aimed to verify the effectiveness of the Nottingham Hip Fracture Score (NHFS) for predicting postoperative outcomes following hip fracture surgery. Methods:This was a single-center and retrospective analysis. A total of 702 elderly patients with hip fractures (age ≥ 65 years old) who received treatment in our hospital from June 2020 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Urinary tract infections (UTIs) significantly contribute to an increased incidence and adverse prognosis in fracture patients, particularly those with hip fractures [ 58 , 59 ]. A retrospective analysis of 93,637 Danish patients with hip fractures revealed that UTIs were a substantial factor associated with elevated mortality rates, specifically in females [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) significantly contribute to an increased incidence and adverse prognosis in fracture patients, particularly those with hip fractures [ 58 , 59 ]. A retrospective analysis of 93,637 Danish patients with hip fractures revealed that UTIs were a substantial factor associated with elevated mortality rates, specifically in females [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following data for patients were collected by reviewing the medical record system: sex, age, body mass index (BMI), hospital stay, smoking history, drinking history, number of co‐morbidities, diabetes, hypertension, osteoporosis, fracture type (garden typing), preoperative nutritional risk score (NRS), and American Society of Anesthesiologists (ASA) score; operative manners (SHA and THA); anesthesia method (general anesthesia and lumbar anesthesia); operation time (> = 2h / joint); preoperative laboratory examination indicators, including white blood cell (WBC), red blood cell (RBC), hemoglobin (HB), hematocrit (HCT), percentage of neutrophils (NEUT%), C‐reactive protein (CRP), serum K + , blood urea nitrogen (BUN), creatinine (CR), albumin (ALB), aspartate aminotransferase (AST), alanine aminotransferase (ALT), international normalized ratio (INR), activated partial thromboplastin time (APTT), fibrinogen (FIB), thrombin time (TT), and prothrombin time (PT); associated operation indicators, including bleeding volume; blood transfusion volume; and postoperative laboratory examination indicators, including RBC, HB, 12,13 ALB, 14,15 K + , 12,16 in agreement with many previous studies. Based on the follow‐up results, the postoperative survival time and death rates of patients were collected.…”
Section: Methodsmentioning
confidence: 99%
“…However, these features are not explicitly included in HF-specific risk assessment tools (e.g. in O-POSSUM only symptoms and clinical findings suggestive of cardiovascular disease are included and NHFS only the number of comorbidities is included as an input parameter) [7][8][9][10]. Moreover, neither PTH or vitamin D levels are included in any of the current tools, despite an increasing number of studies supporting the key role they play in bone metabolism and prevention of fracture [45-57] and, potentially, with increasing recognition of their importance in the immunity [58-60] prevention of post-operative complications such as hospital acquired infections.…”
Section: Feature Importance -Model Interpretation and Shap Analysismentioning
confidence: 99%
“…One key aspect in HF assessment and management challenge is the prognostication of poor short-term outcomes. There exists a substantial amount of analysis from traditional statistical methods (such as logistical regression, LR) in identifying key risk factors for predicting poor outcomes, notably mortality, following HF and scoring tools that have risen to prominence are the Nottingham Hip Fracture Score (NHFS) and the orthopaedic-Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (O-POSSUM) [7][8][9][10]. Most of these tools require a combination of both clinical, laboratory and intra-operative data; and the lack of laboratory and intra-operative data early during admission limits the use of such tools in early risk stratification.…”
Section: Introductionmentioning
confidence: 99%